A miniaturized CPW-fed on-chip UWB monopole antenna with band-notch characteristics. Issue 1 (3rd July 2019) - Mandal, S.; Karmakar, A.; Singh, H.; Mandal, S. K.; Mahapatra, R.; Mal, A. K.
Abstract: This paper presents the design and analysis of a miniaturized, coplanar waveguide-fed ultra-wideband monopole on-chip antenna with band-notch characteristics. By incorporating a "U"-shaped slot in the feedline, a band-notch is realized in the frequency range of 7.9–8.4 GHz to avoid interference from the X-band uplink satellite communication system. The proposed antenna achieved good voltage standing wave ratio (VSWR) characteristics with VSWR value <2 for the frequency range of 2.5–20.1 GHz excluding the band-notched frequencies. The fractional bandwidth and bandwidth ratio are obtained as 156% and 8.04:1, respectively. Dominant factors that affect the center frequency and bandwidth of the notched band are thoroughly investigated. This paper addresses both frequency as well as time domain behavior of the proposed structure. Standard 675 µm thick, high resistive silicon substrate ( ρ ≥8 kΩ-cm, ε r = 11.8, and tan δ = 0.01) is used to design the proposed compact antenna structure with a layout area of 8.5 × 11.5 mm 2 . Fabrication process steps along with simulated and measured data are presented here. A close analogy between simulated and measured data is observed.